Pendekatan Ilmiah (Scientificapproach) dalam Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Kurikulum 2013: Studi Analisis Berdasarkan Paradigma Positivistik - Kholifah, Nur (Didaktika Religia, 2016)
This study reviews the scientific approach of Pendidikan Agama Islam dan BudiPekerti Kurikulum 2013, based on scientific paradigm of positivistic, proposedby Auguste Comte. The results of this study reveal that the scientific approachin the curriculum 2013 is done through some steps: to observe, to question, toreason, to associate and to communicate. This scientific approach is relevant tothe positivistic paradigm. The theory stems from the emergence of legal positivismof Law of Three Stages by Auguste Comte. It states that historical developmentof human thought has evolved in three stages, namely theological or fictitious,metaphysical or abstract, and positive or scientific or real. Thus, according tothis approach, if scientific approach is applied in Pendidikan Agama Islam danBudi Pekerti Kurikulum 2013 in the aspect of Aqidah, it becomes less relevant.However, the aspect of jurisprudence, morality, al Quran hadith, and Islamiccultural history, the scientific approach is very appropriate to be applied into thelearning process.